Principles of Oscillatory Brain Dynamics and a Treatise of recognition of Faces and Facial Expressions - Öniz, Adile; BAŞAR, EROL (ELSEVIER SCIENCE BV, SARA BURGERHARTSTRAAT 25, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2006)
The research of event-related oscillations is one of fast-growing fields in neuroscience. In this study, a theory of the "whole-brain-work," which can be useful for functional interpretation of brain oscillations, is presented together with its application to recognition of faces and facial expressions. Following results are summarized: (1) Mechanisms leading to the perception of the grandmother picture are manifested with parallel activations of neural assemblies in different cortical locations and as superposition of delta, theta, alpha, beta, and gamma oscillations. Known and anonymous faces can be differentiated by means of oscillatory brain dynamics. Percepts cannot be localized in a given specific region. The differentiation of facial expression induces significant change in alpha and theta oscillation. (2) While the importance of fMRI in object recognition is clear, this method has low temporal resolution. Our results shows that multiple brain oscillations clearly differentiate the known and unknown faces with varied degrees of selective-responsiveness in a short time window between 0 and 800 ins, thus completing and implementing the analysis of percepts in the dynamic window and indicating a broader distribution at the cortex. (3) The presented evidence of selectively distributed multiple oscillations for differentiation of facial percepts is in conceptual accordance with the "selectively distributed processing" in neurocognitive networks of Goldman-Rakic, Fuster, and of Mesulam. The large-scale approach of several investigators is also confirmed with the new results. On facial stimuli, a given location can show a considerable selected activation, but the formation of percepts is manifested by multiple oscillations with differentiated weight in large neural populations. (4) The most important feature of the comparison of percepts of grandmother and anonymous faces is the existence of a variety of significant differences in delta, theta, alpha, beta, and gamma responses between the anonymous and grandmother faces in frontal, central, parietal, temporal, and occipital sites. (5) The brain response is a construct in a multi-dimensional state manifested by amplitudes of oscillatory responses, topological coordinates, and changes in the time axis following presentation of the percepts including delays and prolongations, coherence between locations. Only a new metrics embracing all these parameters can be representative for dynamics of functionality in the brain. The conceptual aspects of this new scope are explained in the presented theory.
Keywords: Face Recognition; Facial Expressions; Brain Oscillations; Delta; Theta; Alpha; Beta; Gamma; Phase Locking; Event Related Oscillations; Memory; Brain Theory; Event Related Potentials; Alpha Oscillations; Wavelet Entropy; Cognitive Processes; Theta Oscillations; Fusiform Gyrus; Working Memory; Stimulus Onset; Erp Components; Visual Cortex; Yüz Tanıma; Yüz İfadeleri; Beyin Salınımlar; Delta; Teta; Alfa; Beta; Gama; Faz Kilitleme; Olaya İlişkin Salınımlar; Bellek; Beyin Teorisi; Olaya İlişkin Potansiyeller; Alfa Salınımlar; Dalgacık Entropi; Bilişsel Süreçler; Teta Salınımları; Fusiform Girus; Çalışan Bellek; Uyaran Başlangıçlı; Erp Bileşenleri; Görsel Korteks